2018
DOI: 10.11114/jets.v6i3.2884
|View full text |Cite
|
Sign up to set email alerts
|

Irrational Beliefs in Romantic Relationships as the Predictor of Aggression in Emerging Adulthood

Abstract: The purpose of this study is to examine irrational beliefs in romantic relationships as the predictor of aggression in emerging adults. The study is a quantitative study done using the relational survey model. The study group is composed of 351 fourth-year students, 201 females and 150 males, who were attending three universities in Central Anatolia during the 2016-2017 academic year. In order to collect the study data, 23-item "KAR-YA Aggression Scale with four sub-dimensions (Physical Aggression, Hostility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
6
1
5
Order By: Relevance
“…A research by Gündoğdu et al found male aggression to be high and this was explained by the social roles attached to men and women (Gündoğdu et al, 2018). Another study by Winstead & Derlega on marriage relations also used gender as one of the most researched variables because the majority of the differences between men and women in society is associated with its roles (Winstead & Derlega, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A research by Gündoğdu et al found male aggression to be high and this was explained by the social roles attached to men and women (Gündoğdu et al, 2018). Another study by Winstead & Derlega on marriage relations also used gender as one of the most researched variables because the majority of the differences between men and women in society is associated with its roles (Winstead & Derlega, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Winstead & Derlega on marriage relations also used gender as one of the most researched variables because the majority of the differences between men and women in society is associated with its roles (Winstead & Derlega, 1993). It has also been discovered that having irrational beliefs about gender differences in marriage is associated with aggression in adulthood which is a significant predictor of physical and verbal aggression as well as hostility and anger (Gündoğdu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Namun, meskipun tindakan agresif tidak mengakibatkan rasa sakit dan cedera fisik, namun dapat menyebabkan cedera psikologis yang tidak tampak (Stubbs & Dickens, 2009). Penelitian oleh Gündoğdu, Yavuzer, & Karataş (2018) menunjukkan bahwa agresi laki-laki menjadi lebih tinggi dikarenakan peran sosial yang melekat pada laki-laki dan perempuan. Sehingga kepercayaan terhadap perbedaan gender tersebut menjadi prediktor terjadinya agresi verbal dan fisik dalam rumah tangga.…”
Section: Kepribadian Agresifunclassified
“…In the literature review, it was determined that as the interpersonal cognitive distortions were increased in married individuals, tolerance and marital adjustment were decreased, while marital conflicts were increased 15–17 . In addition, interpersonal cognitive distortions have been found to increase stress, anger, and aggression 18–21 …”
Section: Introductionmentioning
confidence: 99%